Mentoring as social learning value creation in two South African environmental organisations: a social realist analysis - Hiestermann, Michelle (Rhodes University, Faculty of Education, Department of Education)
South Africa is facing overwhelming crises of educational quality, record rates of unemployment (especially amongst youth) and environmental issues and risks, further exacerbated by the Covid-19 pandemic. Environmental education research that addresses these challenges is critical to ensuring that future generations thrive in a warming climate. South Africa needs environmental leaders; we therefore need to understand and explore the possibilities of mentoring young professionals in environmental organisations in South Africa. Several initiatives have been developed to contribute to the mentoring of young professionals in South African environmental organisations. This study drew on a critical realist ontology, social realist meta-theory and domain specific theory on mentoring and evaluation to explore mentoring as a value creating proposition in two environmental organisations in South Africa that were part of the national Groen Sebenza youth employment creation programme which had a strong focus on mentoring. To strengthen conceptual analytical tools on mentoring, I undertook an immanent critique of domain specific mentoring theory to develop a more appropriate foundation for mentoring theory in the environmental sector that was not subject to the historical influence of human capital theory only (which has tended to dominate the field's literature). I then developed in-depth understanding of mentoring in two case study contexts, namely a non-profit environmental organisation and an environmental consulting company, using qualitative research approaches that included contextual profiling, case study research and mirror data workshops. Analytically, I considered the case data drawing on the value creation evaluation framework of Wenger-Trayner and Wenger-Trayner (2014) which itself was developing as an analytical framework as the study developed. I strengthened the analytical framework with social realist interpretations drawing on Archer (1995). This offered me a way of developing an in-depth understanding of the factors which constrain or enable the value creation possibilities of mentoring, with a view to inform human capacity development initiatives that support mentoring in the environment sector. It was possible to explain the value creation possibilities of mentoring within two case study environmental organisations through considering mentoring as a social learning process of value creation and this overcame some of the shortfalls identified in other early learning theories as well as theories of mentoring. The research revealed how mentoring can provide a value creation social learning trajectory for unemployed youth. A social realist perspective explained how young professionals expanded their primary agency, through full participation in workplace communities of practice, to find their identity as corporate agents in the workplace with their mentors. In this research, Social Realist ontology, theory and methodology was able to achieve what Human Capital Theory could not and provided an account of the interplay of structure, culture and agency over time, through emergent properties and the separation of structure and agency. Thus, it was possible to avoid conflation and the limitation of theory of the present tense, with a deeper, ontologically robust explanation of mentoring as social learning and social change and a social realist orientation to human capacity development. South Africa has a history of oppression, inequality and injustice and requires social processes that are reflexive, critical, emancipatory and transformative. Therefore, this research required theory and approaches that could explain mentoring of unemployed youth, as a common good initiative for a more just and sustainable society. As shown in this study, a Social Realist approach can uncover the underlying generative mechanisms and make the implicit more explicit in research, policy and strategy, offering a robust alternative to the tenets of Human Capital Theory that have driven much mentoring research in South Africa and elsewhere to date.
Keywords: Social realism; Social learning; Mentoring; Environmental education -- South Africa